Rotational speed modulation used with continuous-flow left ventricular assist device provides good pulsatility. (10th August 2017) - Naito, Noritsugu; Nishimura, Takashi; Iizuka, Kei; Takewa, Yoshiaki; Umeki, Akihide; Ando, Masahiko; Ono, Minoru; Tatsumi, Eisuke
Abstract: OBJECTIVES: Continuous-flow left ventricular assist devices (CF-LVADs) are widely used to treat patients with end-stage heart failure. Although continuous flow is different from physiological flow, patients show improved outcomes after CF-LVAD implantation. A novel rotational speed (RS) modulation system used with CF-LVAD (EVAHEART) has been developed, which can change RS in synchronization with the native cardiac cycle. We conducted the present study to investigate the influence of the system on pulsatility in peripheral perfusion. METHODS: We implanted EVAHEART devices at the left ventricular apex drainage and the descending aortic perfusion via a left thoracotomy in 7 adult goats (56.8 ± 8.1 kg). Cardiogenic shock was induced by a beta-adrenergic antagonist. We evaluated the pulsatility index and maximal time derivative of flow rate (max dQ/dt) of the carotid, mesenteric and renal arteries. These data were collected with a bypass rate of 100% under 4 conditions: circuit clamp, continuous mode, co-pulse mode (increased RS during systole) and counter-pulse mode (increased RS during diastole). RESULTS: The pulsatility indexes of the carotid and renal artery in the co-pulse mode were significantly higher than in the other modes. Max dQ/dt of the carotid and mesenteric arteries were significantly higher in the co-pulse mode than in the counter-pulse mode. CONCLUSIONS: The co-pulse mode of this novel RS modulation system may provide better pulsatility not only in the large vessels but also in the peripheral vasculature.